Research advances in prevention and treatment of burn wound deepening in early stage - Lu, Meiqi; Zhao, Jie; Wang, Xiaochuan; Zhang, Jingjuan; Shan, Fei; Jiang, Duyin (Frontiers in Surgery, 2022)
The burn wound is a dynamic living environment that is affected by many factors. It may present a progressive expansion of necrosis into the initially viable zone of stasis within a short time postburn. Therefore, how to salvage of the zone of stasis is of crucial importance in prevention and treatment strategies of burn wound progressive deepening. This review focuses on the cellular basis of tissue injury and the current progress of prevention and treatment strategies of burn wound progressive deepening, in order to provide references for the treatment of burn wounds in the early phase.